Perlakuan Akuntansi Sektor Publik Desa - I Made Laut Merthajaya (Universitas Gorontalo, 2019)
This study aims to analyze and find out the procedures for preparing accountability reports in Kebondalem Prambanan Village associated with Minister of Home Affairs Regulation No. 113 of 2014. This study discusses accounting policies, the budgeting process, and budget execution. This paper is based on descriptive research that explains the accounting behavior of village public sector in Central Java. The scope of village entity financial transactions is relatively smaller than the local government, but includes all accounts contained in the local government. The results of this study conclude that the accounting policy adopted by the village government of Kebondalem Kidul has been in accordance with the existing government order. In addition, the existence of a village-based accounting information system, such as Siskeudes, shows that the village government of Kebondalem Kidul has taken seriously the presentation and preparation of its accountability reports so far. The posts in the APBDes Realization Report are also in accordance with Permendagri No. 113 of 2014 and the allocation of Village expenditure is in accordance with Government Regulation No. 43 of 2014.